KEANEKARAGAMAN POHON PENGHASIL BUAH DI HUTAN SEKUNDER PADA AREAL IUPHHK-HTI PT. BHATARA ALAM LESTARI KABUPATEN MEMPAWAH - Afronius, .; Herawatiningsih, Ratna; Manurung, Togar Fernando (JURNAL HUTAN LESTARI, 2018)
The puposes of this research is to examine the diversity of fruit-producing trees that can be consumed. The object of this research are all fruit-producing trees in the plot or observation path, which is the limitation is the fruits that can be consumed by human. This research have been done at IUPHHK-HTI PT. Bhatara Alam Lestari. The printed path has been used to determine the plots and observation paths of fruit-producing trees diversity that can be consumed on the ground. The result of the research found that there are 12 kinds of tree producers offorest fruit consumption, they are asam-asam, cempedak hutan, durian hutan, jungkang, kandis, kelampai, keranji, medang asam, nyatoh/sangai, petai hutan, rambutan hutan, ubah. The value of the dominant index (C) at the research area is quite poor, because the value of the dominant index from all the lane is not reached the highest index value of dominance yet (C-1). This indicates that the community not found one or two tree producing fruit consumption who dominated on a community forest secondary , while index value diversity its kind low because less than the value 1 , this showed that on a community many those kinds of composing under each organizations research is low. To value index provided the global financing of other firms ahmad abundance of offerings shared with or far higher than those, because the pattern of spreading on this community can be equally on each its kind.Keyword: Diversity, tree producing fruit, secondary forest